EKSISTENSI AKTIVIS PEREMPUAN DALAM MEWUJUDKAN PERDAMAIAN DI ACEH - Ismiati Ismiati (Fakultas Dakwah dan Komunikasi Universitas Islam Negeri (UIN) Ar-Raniry, 2016)
This study aims to identify and understand the existence and traces of female activists humanitarian trip in building peace in Aceh. This research arena is Acehnese women activists involved in various humanitarian missions. How their existence from the time of the conflict until peacetime in order to establish peace in Aceh as a heroic sacrifice of humanity . This study uses a qualitative approach . Information was obtained from informants to interview and FGD (focus group discussion). The results showed that gait women activists can be seen from the various activities in social, political, both in situations of conflict and in peace. Women fought and played a strategic role to defend themselves, their families and communities, both at the community level as well as socio-political level. They are active in capacity building, empowerment and contribute to development